FORMULATING EFFECTIVE MARKETING STRATEGIES TO ENHANCE THE CASA RATIO OF ISLAMIC BANKS: AN APPLICATION OF ISO 31000 RISK MANAGEMENT - Dedi Nestoriko Sinaga; Bramantyo Djohanputro; Melinda Malau (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aims to formulate effective marketing strategies for increasing Current Account and Savings Account (CASA) based on risk management in Islamic banks with a case study of a bank in Indonesia, which is pseudonymized as Bank PODA. During the 2022–2024 period, Bank PODA's CASA performance showed a declining trend, requiring strategic initiatives to improve the efficiency of the Cost of Fund (CoF) and the bank's profitability. This study employs a combination of qualitative methods with a descriptive approach and quantitative research methods. The results indicate that internal factors influencing the low CASA include limited branch networks, suboptimal marketing team capacity, limited e-channel features, and delays in strategic IT projects. External factors encompass the increase in the BI reference interest rate, intense competition from digital banks offering high margins, low Islamic banking literacy, and a shift in customer behavior towards investment instruments compared to bank products. The recommended strategies include strengthening products targeted at Muslim communities, developing a cash management system and Islamic digital features, establishing a special team for penetrating the Muslim segment, enhancing the capacity of marketing human resources (HR), and forming non-branch networks. The implementation of these strategies must be accompanied by risk management based on ISO 31000 to mitigate technical, operational, reputational, and other risks, ensuring sustainable CASA growth is achieved.